The Effect of Presenteeism on Employee Performance with Quality of Work as an Intervening Variable in North Binjai District - Akmal Fachruddin Kahar; Isa Indrawan (Lafadz Jaya Publisher, 2023)
The purpose of this study was to analyze the effect of Presenteeism on Employee Performance with Quality of Work as an Intervening Variable. This research was conducted at the North Binjai District Office. The population in this study was 70 employees and all employees were used as samples (saturated sample technique). This research model uses path analysis. Data collection was carried out by distributing questionnaires. The tool for measuring research is Smart PLS. The results of the research are as follows: Quality of Work has an effect on Employee Performance, Presenteeism has no significant positive effect on Employee Performance. Presenteeism has a positive and significant effect on work quality. Quality of work is able to influence presenteeism indirectly on employee performance.